Racial/Ethnic Differences in Cigarette Use Trends in the United States among Multiracial and Other Youth, 1994-2008. (January 2018) - Goings, Trenette Clark; Hidalgo, Sebastian Teran; McGovern, Patricia P.
Tobacco use among the multiracial population is grossly underresearched. This study explored the cigarette-smoking trends of multiracial individuals over time in comparison with monoracial individuals and assessed the relationship between cigarette smoking and factors at the individual, family, peer, school, and state levels. This study used data collected by the National Longitudinal Study of Adolescents and Adult Health from 1994 to 2008. This study examined a subsample of 9, 421 respondents who self-identified as Black, Asian, American Indian, Hispanic, White, or multiracial. Generalized estimating equations were used to analyze the population-level data. Findings suggest that multiracial individuals reported high rates of cigarette use over time. The most consistent correlates of cigarette use were family factors, peer cigarette use, and school policies that prohibit staff from smoking on school premises. Additional research is needed to identify the correlates and causes of cigarette use among multiracial adolescents and young adults.